Detection of circulating antigens of Parastrongylus cantonensis in human sera by sandwich ELISA with specific monoclonal antibody - Eamsobhana, Praphathip; Mak, Joon Mah; Yong, Hoi Sen (SEAMEO Regional Tropical Medicine and Public Health Network, 1997)
A specific monoclonal antibody (AW-3C2) as revealed by ELISA was produced against the adult worm antigens of Parastrongylus cantonensis and used in a sandwich ELISA for the detection of circulating antigens in the sera of parastrongyliasis patients and those with other parasitic diseases. A total of 60 sera was used in this study. Of these, 10 each were from patients with parastrongyliasis filariasis, gnathostomiasis, malaria and toxocariasis. The control group consisted of 53 serum samples from normal healthy Thais and Malaysians. The mean +/- optical density (OD) values for the normal Thai and Malaysian groups were 0.126 +/- 0.028 and 0.124 +/- 0.029, respectively. Mean OD values of parastrongyliasis patient group differed significantly from that of the normal groups as well as those of other parasitic infections. Using a cut-off point of mean OD +/- 3SD of the normal control groups as indicating a positive reading, the specificity of the assay with this monoclonal antibody was 100% while the sensitivity was 50%.